Mulheres empreendedoras no mercado de trabalho: dificuldades e motivações. - Fenelon, Beatriz Carvalho (2020)
Historically, women are gaining more prominence in society through the struggle for their rights, and as a consequence, undertaking and conquering spaces in the labor market. Thus, the present study seeks to know the profile, difficulties of women entrepreneurs and their motivations for entrepreneurship. The questioning that guided the study is based on what are the most important characteristics for an entrepreneurial woman? What are the challenges and their motivations? Methodologically, a descriptive exploratory research with quantitative and qualitative analysis was used with questionnaires applied by the google forms platform in a group of Women from Brazil As a result, the most important characteristics were initiative (70.6%), followed by taking a risk, emotional intelligence, ambition and leadership. Challenges to be overcome are discrimination in the labor market, bureaucracy, lack of training, among others. The difficulties were discrimination and prejudice. The reason for which they started to undertake, 61.8% was their financial / personal independence, the reason for wanting to be their own boss and complement the family income. In the face of the challenges faced, there was a double journey, prejudice, investment inequality and access to credit.